(untitled) (Research, Society and Development, 2020)
The objective of this study was to obtain information with scientific validity regarding the probable physiological alterations that sheep may suffer in the period prior to slaughter and its relationship with welfare conditions and maintenance of homeostasis. Twenty-nine castrated male lambs were used, clinically healthy, with no defined breed, and aged up to one year. Before slaughter, the heart and respiratory frequencies were measured, as well as the rectal temperature. At the time of bleeding, a blood sample was collected for analysis of hematological parameters (lactic acid, glucose, hematocrit). The mean value found for the rectal temperature was 39.30 ± 0.45 °C, for respiratory rate of 64.10 ± 28.52mov/min, heart rate of 106.90 ± 30.57bat/min, lactic acid of 4.81 ± 1.04mmol/L, glucose of 69.79 ± 10.33mg/dL and hematocrit of 38.93 ± 3.28%. The database analysis showed a low and positive correlation between respiratory rate and rectal temperature. It was concluded that lambs kept at high temperatures showed an increase in respiratory and cardiac frequencies, as well as an intensification of the stress condition reflected by the increase in plasma lactic acid levels.